Study in Correlation between Senile Cataract and Serum 25-Hydroxyl Vitamin D Insufficiency (Medico Legal Update, 2021)
Background: Study in correlation between Senile cataract and Serum 25-Hydroxyl Vitamin D Insufficiency.Mean Value of vitamin -D less than 10ng/ml seen in group-1 which show severe deficiency. Mean Levelof vitamin-D in group-2 15-24 ng/ml which show mild to moderate deficiency. There was a statisticallysignificant difference in both groups.(p value-